Improving Australia's flood record for planning purposes – can we do better?. Issue 1 (2nd January 2020) - Allen, KJ; Hope, P; Lam, D; Brown, JR; Wasson, RJ
ABSTRACT: Extreme rainfall is projected to increase with climate change, but the impact of climate change on floods is uncertain. Infrastructure design based on information available from short gauged time series (typically ~30 – 80 years) may not take account of the full range of possible flood events, or be suitable for identifying non-stationarity. Australian palaeoflood and palaeo-hydroclimate records drawn from a wide variety of natural archives and documentary sources suggest that Australia has been subjected to larger flood events in the past; a pluvial period for eastern Australia in the eighteenth Century is particularly note-worthy. If the current infrastructure is inadequate for past floods, it is unlikely it will adequately mitigate future floods. We discuss how improved awareness, and incorporation, of palaeoflood records in risk estimates could help guide infrastructure planning and design, flood event prediction and inform flood mitigation policy. This is particularly relevant for Australia with its notoriously variable hydroclimate.